Perubahan Paradigma Pendayagunaan Sumberdaya Air dan Implikasinya Terhadap Strategi Pengembangan Produksi Pangan - nFN Sumaryanto; Tahlim Sudaryanto (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2001)
EnglishIn line with population growth and economic development, available fresh water per capita decreases continously. Refer to the trend, sufficient renewable fresh water for the future will depend on the implementation of new paradigm in water resource development initiated by declaration of